Update on nanofillers in nanocomposites from introduction to application - Haghi, A. K. (Smithers Rapra, 2013)
Polymer nanocomposites continue to receive widespread acclaim for their potential to improve composite materials beyond the use of conventional macroscale fillers. Nanofillers in nanocomposites are used in a broad range of applications because their ease of processing, low price and a combination of advantageous properties. In the last decade, nanofiller particles have prompted much attention and become a developing field in nanocomposites. The main objective of this book is to show how a particle size at the nano scale offers a large surface area and good dispersion behaviour. Detailed inform.
Keywords: Nanocomposites (Materials); Polymeric composites.; elektronické knihy; electronic books